Deep Inferior Epigastric Perforator Flap Preconditioning Using Selective Vessel Ligation (Delay Procedure) and Thinning Liposuction - Alberto Franchi, MD; Caterina Marra, MD; Gian Piero Mantovani, MD; Florian Jung, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. The deep inferior epigastric perforator (DIEP) flap is the gold standard in autologous breast reconstruction, but it is rarely used for superficial limb defects due to its excessive thickness. In this case report, we describe the innovative use of the DIEP flap for reconstructing a large, shallow defect on the anterior thigh of a 21-year-old man, previously treated with split-thickness skin grafts. To achieve a large yet thin and well-vascularized flap, we combined 2 techniques: the surgical delay procedure and liposuction. The patient, with a body mass index of 26 kg/m², sought cosmetic and functional improvement for his left thigh, agreeing to the use of abdominal tissue, which also allowed for volume reduction of the abdomen. However, the abdominal flap was too thick for an aesthetic result, and the flap to be harvested was too large to be adequately vascularized by a single pedicle. After evaluating the vascular anatomy with Doppler ultrasound and computed tomography angiography, we planned a 2-stage operation: first, a surgical delay procedure to enhance perfusion of the main pedicle, and later, liposuction of the subcutaneous tissue before flap transfer. The postoperative course was uneventful, with only minimal superficial necrosis managed conservatively. The patient declined further corrective procedures, as he was satisfied with the result. This case represents the first reported combination of flap thinning through liposuction and the delay technique for a DIEP flap. It offers a novel approach for large superficial defects when immediate coverage is not required, providing a potential solution for obtaining a thin, well-perfused flap.